Animals at the zoo make me emotional: Can animal behavior affect visitor conservation behaviors? - Laketa, Morgan (East Carolina University)
Zoos are a popular form of entertainment where viewing animals is used to promote conservation. Research has explored the efficacy of zoos promoting pro-conservation behavior (PCB) as well as how zoos shape the viewing experience to promote conservation goals. Studies have found visitors' viewing and interactions with animals create empathy-based reactions creating a sense of connection with the animal which can be linked to pro-conservation behavioral intentions (PCBI). In turn, PCBI has been found to link to PCB post-visit but is under-researched. Additionally, visitors' emotions have been found to influence engagement in PCB; however, this relationship is still not fully understood. The purpose of this study is to explore visitors' emotional responses to animal activity and how this influences PCBI. A total of 241 zoo visitors were surveyed regarding the animal they found to be most interesting during their visit, reactions to the viewing experience, PCBI, and PCB they performed prior and during their visit. Results revealed that animal behaviors have an effect on the zoo visitor's connection to that animal. There was a positive relationship between visitor connection to animals and PCBI. Retail-related PCB is encouraged in zoos as part of promoting conservation as well with results revealing that most onsite PCB was retail-related.
Keywords: pro-conservation behaviors; conservation behavioral intentions; connection; Zoo visitors--Attitudes; Zoo animals--Conservation; Zoo animals--Behavior; Environmental health; Environmental ethics